Potential production of transparent P CuGa02/ n ZnO Heterojunction thin film Diodes - Afishah Alias (Universiti Malaysia Sabah, 2012)
Transparent electronic is a new frontier in electronic industry. Most transparent semiconducting oxides that are being intensively studied are n-type material such as ZnO ZnO is one of the most promising transparent semiconductor oxide that can be apply in various electronics and optoelectronics devices. However ZnO has n-type conductivity and reported very difficult to obtain p-type of ZnO, which is owing to the lack of suitable p-dopants and many electrons supplies by impurities and lattice defects in ZnO. The development of p-type materials is much desired as this would open up the applications of new transparent devices. Recently, Cu-based oxide semiconductors such as delafossite CuMO (M = AI, Ga, In) have been widely studied for p-type materials using various deposition methods. A CuGa02 film is a promising material for p-typetransparent conducting oxide. Thus, in order to fabricate p-n junction with n- ZnO, delafossite CuGa02 is proposed as p-type material, due to its smaller lattice mismatch with ZnO. In this research ZnO films and CuGa02 films have been fabricated by sputtering method. The optimum deposition parameter for ZnO films and CuGa02 films were Investigated.